THE PRINCIPLES OF Music education in Austria and a comparison with the pedagogical practices for classical guitar in Austria and Bulgaria - Pavlova, Bozhana (Young Scientific Music and Dance Forum : Conference with international participation, 2020)
The present report focuses on the specific characteristics of classical guitar education and music studies at Austrian music schools. The detailed analysis of the curriculum, the recommended literature and the teaching methods will outline the common pedagogical practices there. Furthermore, it will define the didactic, pedagogical and psychological aspects of the curriculum which aim to develop the emotional sensibility and music aesthetics of the students. The focus of the education in Austrian music schools is on establishing a long-term relationship with the instrument and developing musical creativity. The report presents a comparison between the pedagogical methods in Austria and Bulgaria, and presents its conclusions from the presented arguments and theses. Finally, it draws a parallel between the guitar music education of pupils in both countries.